The importance of predator species in the population dynamics of the Brown hares (Lepus europaeus, Pallas 1778) – Literature review - Farkas, Péter; Kusza, Szilvia; Majzinger, István (Acta Agraria Debreceniensis, 2017)
One of the conditions for successful small game management is the good management of predator species. The predator species play an important role in the sustainable utilization of the domestic brown hare populations. A portion of these species are under nature protection and with the rest of the species can be utilizing by the wildlife management professionals. Important prey species of brown hares: perspective are red fox, domestic dog and domestic cat. Based on latest date of the National Game Management Database in hunting bags increasing every year the number of the European badger, the stone marten and the golden jackal. In Hungary the brown hare’s most important predator bird species are common buzzard, marsh-harries and goshawk. The human race is not only as a top predator affects the number of the population of brown hares with the wildlife management but indirectly with traffic, (soil cultivation, mowing, and pest control) as well. The control of predators is absolutely necessary for successful small game management, but without sufficient habitat size and habitat development it is hardly sufficient.